2021
DOI: 10.3390/ma14144011
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Mechanical Effect of Free Water on the Dynamic Compressive Strength and Fracture of High-Strength Concrete

Abstract: It is well-known that the effect of interstitial fluid on the fracture pattern and strength of saturated high-strength concrete is determined by qualitatively different mechanisms at quasi-static and high strain rate loading. This paper shows that the intermediate range of strain rates (10−4 s−1 < ε˙ < 100 s−1) is also characterized by the presence of a peculiar mechanism of interstitial water effect on the concrete fracture and compressive strength. Using computer simulations, we have shown that such a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 82 publications
(174 reference statements)
0
2
0
Order By: Relevance
“…Numerous experimental studies have confirmed that the dynamic compressive strength of rocks apparently exhibits a positive correlation with the loading rate or strain rate in a certain range, and that when the strain rate increases, the dynamic compressive strength of the rocks increases [34,35]. The fitted relationship between the dynamic compressive strength and the average strain rate pertaining to the rock specimens that are subjected to different states is depicted in Fig 5(A) [36,37].…”
Section: Plos Onementioning
confidence: 93%
“…Numerous experimental studies have confirmed that the dynamic compressive strength of rocks apparently exhibits a positive correlation with the loading rate or strain rate in a certain range, and that when the strain rate increases, the dynamic compressive strength of the rocks increases [34,35]. The fitted relationship between the dynamic compressive strength and the average strain rate pertaining to the rock specimens that are subjected to different states is depicted in Fig 5(A) [36,37].…”
Section: Plos Onementioning
confidence: 93%
“…In comparison with classical DEM, the method of homogeneously deformable discrete elements allows accounting for the stress–strain state of the elements, including their volume strains [ 39 , 40 , 44 , 45 ]. It also allows for more accurate implementation of mechanical strength criteria, including the Drucker–Prager criterion.…”
Section: Methodsmentioning
confidence: 99%